FORMULATION AND EVALUATION OF FAST DISSOLVING TABLET OF KETOROLAC TROMETHAMINE - G, Sangeetha; PG, MAHESH; K, CHANTHINI; M, LOKESH; S, AMEEN (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Aim: Ketorolac tromethamine is used for the treatment of a number of infections including infection of joints and bones, gastroenteritis, malignant otitis externa, respiratory tract infections, cellulitis, urinary tract infections, anthrax, skin structural infections, and typhoid fever, and it also used in the treatment of community-acquired pneumonia, chronic bacterial prostatitis, and nosocomial pneumonia. Objective: Difficulty in swallowing (dysphasia) is a common problem of all age groups, especially the elderly and pediatrics, due to physiological changes associated with these groups. Conclusion: In the present work, it has been observed from all formulations of pre-compression and post-compression studies were given within the limit of values. The in vitro dissolution data, F1 (combination of different superdisintegrants) when compared to other formulation.